COMPRESSION AND FLEXURAL PROPERTIES OF FINGER JOINTED MANGO WOOD SECTIONS - V.S Kishan Kumar (Maderas. Ciencia y Tecnología, 2015)
In this paper, an attempt was made to assess the effectiveness of finger jointing in utilising mango wood sections for various end uses like furniture. The study was based on the estimation of Modulus of elasticity and Modulus of rupture under static bending and Maximum Crushing Stress and Modulus of elasticity under compression parallel to grain of finger jointed sections and comparing them with the values measured for clear wood sections from the same lot. For joining the sections, the Poly Vinyl Acetate and Urea Formaldehyde adhesives were used. It was found that the Modulus of elasticity of the sections joined by either adhesive showed significantly better values than that of unjointed clear wood sections. The Modulus of rupture values of sections joined with Urea Formaldehyde were similar to those of unjointed clear wood sections. However, sections jointed with Poly Vinyl Acetate adhesive exhibited lower Modulus of rupture. Under compression, the parameters of the jointed sections joined with either adhesive were either similar or better than those of the unjointed clear wood sections. The study demonstrates the utility of finger jointing of mango wood sections for furniture parts especially with the Urea Formaldehyde adhesive.